(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Modern ballistic protection equipment is lightweight, flexible, and withstand multiple types of threats. Depending on their purpose, they are assembled from various materials, with ceramic plates and composites based on high-performance polymer fibers finding wide application in recent years. Multilayer fabrics with different textures woven from synthesized special mechanically high-resistant polymer fibers successfully withstand the high-speed and high-energy impact of the striking element. Given the risk of exposure to radiation during military conflicts or industrial accidents, it is necessary to know the anti-radiation parameters of protection means. The report attempts to establish the degree of protection against photon radiation in the range of 40 KeV to 120 KeV for samples of ballistic panels with ballistic protection levels III+, III++, and IV. The degree of attenuation of photon radiation with these energies was measured by irradiating the examined ballistic panels. A dose-dependence has been obtained with level of ballistic protection for the specific material as a function of the energy of photon irradiation.